Identifying Pathways for Climate-Resilient Multispecies Fisheries - Karr, Kendra A.; Miller, Valerie; Coronado, Eva; Olivares-Bañuelos, Nadia C.; Rosales, Martha; Naretto, Javier; Hiriart-Bertrand, Luciano; Vargas-Fernández, Camila; Alzugaray, Romina; Puga, Rafael; Valle, Servando; Osman, L. P.; et al. (Frontiers in Marine Science, 2021)
Fish live in communities, and most fisheries catch multiple species, yet fishery management predominately focuses on single species. In many multispecies fisheries, a variety of species are generally caught together at similar rates. Failure to account for this adequately in management has resulted in serial depletion and alterations to the ecosystem. Ideally, multispecies fisheries management should strive to produce good yields from specific valuable stocks and avoid adverse impacts of fishing on marine ecosystems. Moreover, multispecies management should aim to build resilience to changes in stock productivity and distribution driven by climate change. Here, we present tools and pathways that seven fisheries are adopting to achieve these goals. These case studies – from Mexico, Cuba, and Chile – differ in data richness, governance structure, and management resources. The management systems are also in various stages of evolution from unmanaged to complete management of a single species but transitioning to multispecies management. While various analytical tools and decision-making processes are described in the case studies, a common feature is the use of participatory stakeholder processes to build capacity and socialize the importance of multispecies management. We use lessons from these cases to recommend a multispecies management approach to overcome the limitations of current practices (typically single-species catch limits or large spatial restrictions), using the participatory processes and data-limited assessments to create stock complexes that simplify multispecies management (i.e., the “fish baskets” approach). Indicator species for each fish basket are identified to support the development of fishery performance indicators, reference values, harvest control rules, and management measures to create an adaptive management cycle to enhance the fishery’s resilience to impacts induced by climate change and other factors.